Creating brand awareness through the production of cheese - Griffiths, Steven (The IIE, 2018)
Attention to environment has become increasing important in human life, as a key element in political decisions, organizational structure and alternatively the well-being of a country. both businesses and consumers are concerned about the environment and the future of our planet. In the business arena, this concern has translated into environmental or green marketing. This research uses qualitative approach to green marketing strategies and what green marketing strategies are and how brands could practice green marketing strategies to the theories and recommendations in the area of green marketing with the aim to gain competitive advantage. The increase in pollutions and environmental damage, and thus increasing public concern in relation to their surrounding natural environment, has started to show off their purchase and consumption behaviors and lead to the creation of a new group of consumers as the green consumers. Green consumers or environmentally friendly consumers refer to those consumers who have examined the effect of goods production and consumption in their purchasing behavior and relevant activities in the markets and decide accordingly.
Keywords: Green marketing; Environmental impact; Consumer behaviour; Green consumer; Brand awareness; Green consumerism